Spiritual Self-Improvement as a Factor of Value Stability in the Rapidly Changing Modern World - Hudzenko, Olena (Skhid, 2026)
The article is devoted to a comprehensive philosophical and anthropological study of spiritual self-improvement as a fundamental factor in the formation of value stability in the conditions of “fluid modernity.” The relevance of the topic is determined by the profound crisis of meaning in consumer society and the challenges of the digital age, which lead to the fragmentation of human consciousness and the relativization of moral ideals. The author argues that in conditions of global instability and military crises in Ukraine, external restructuring of life without transformation of the inner spiritual essence of a person is not capable of ensuring the desired results for the sustainable development of society. The study reveals the anthropological dimension of self-realization, where a person appears as a spiritual and existential basis of being, striving for the realization of supra-personal meanings. The author argues that true self-realization in the 21st century is a challenge that requires the individual to search for higher meanings (the tradition of seeking God), which become the foundation for subjective autonomy. Particular attention is paid to the mechanism of achieving anthropological integrity—the harmonious unity of spirit, soul, and body, which acts as a reliable “immunity” against manipulative technologies and the market logic of “utility.” The role of traditional spiritual practices, in particular Hesychasm and asceticism, which in Ukrainian spiritual culture are considered as means of self-realization and the formation of an internal foundation of values, is highlighted. It has been proven that spiritual self-improvement has a distinct social effect: a spiritually mature personality moves from the model of a passive consumer to the ethics of co-creation and active citizenship. This ensures the transformation of social interaction—from pragmatic calculation to the ethics of “love for one’s neighbor,” which is a guarantee of real inclusion and social justice. The results of the study show that the integration of individual and collective spiritual practices is an important basis for the systemic cultural resilience of the Ukrainian people. The author emphasizes the strategic role of spiritual improvement in strengthening national identity and ensuring the post-traumatic growth of society in conditions of military crisis.